A RARE CASE OF AN ADRENOCORTICAL ADENOMA MANIFESTING WITH PERIODIC PARALYSIS IN A 39-YEAR-OLD WOMAN - Sekarsari, Yulia; Pramono, R. Bowo; Ikhsan, M. Robikhul; Susanti, Vina Yanti; Sinorita, Hemi; Puspitasari, Metalia (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE Periodic paralysis is a rare manifestation of primary hyperaldosteronism. This case demonstrates that primary hyperaldosteronism should be included in the differential diagnosis of periodic paralysis, especially in patients with hypertension. In this case, a 39-year-old Indonesian female was admitted to the hospital with the main complaint of a three-year history of recurring weakness of all four extremities. The patient said she was on therapy for hyperthyroidism and hypertension. Blood tests revealed potassium 1.6 mEq/L. A right adrenal tumor was discovered during a CT scan of the abdomen with contrast. The patient was then treated with a unilateral adrenalectomy. Histopathological examination which showed an adrenocortical adenoma. Primary hyperaldosteronism is caused by an aldosterone-producing adrenal adenoma. Patients may experience sporadic temporary paralysis due to severely low blood potassium levels. A CT scan or MRI can be utilized to diagnose the adenoma. The patient's condition progressively improved following the adrenalectomy.